Voluntary Disclosure of Evaded Taxes - Increasing Revenues, or Increasing Incentives to Evade? - Dominika Irma Langenmayr (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Many countries apply lower fines to tax evading individuals when they voluntarily disclose the tax evasion they committed. I model such voluntary disclosure mechanisms theoretically and show that while such mechanisms increase the incentive to evade taxes, they nevertheless increase tax revenues net of administrative costs. I then test the effects of voluntary disclosure in two separate empirical analyses. First, I confirm that voluntary disclosure mechanisms increase tax evasion, using the introduction of the 2009 offshore voluntary disclosure program in the U.S. for identification. Second, I quantify the tax revenues of voluntary disclosures by considering how some state-level governments in Germany bought whistle-blower data from foreign bank employees, thereby increasing the detection probability and the usage of voluntary disclosures.
Keywords: H26; K42; H24; 330